Site Evaluation Form for Selecting the Right Tree for Your Planting Site - Edward F. Gilman (EDIS, 2002)
This document is ENH869, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date July 11, 2002.